Combined PDF and Rietveld studies of ADORable zeolites and the disordered intermediate IPC-1P. Issue 36 (16th August 2016) - Morris, Samuel A.; Wheatley, Paul S.; Položij, Miroslav; Nachtigall, Petr; Eliášová, Pavla; Čejka, Jiří; Lucas, Tim C.; Hriljac, Joseph A.; Pinar, Ana B.; Morris, Russell E.
Abstract : The disordered intermediate, IPC-1P, formed from the ADORable zeolite UTL has been structurally confirmed using the pair distribution function (PDF) technique. Abstract : The disordered intermediate of the ADORable zeolite UTL has been structurally confirmed using the pair distribution function (PDF) technique. The intermediate, IPC-1P, is a disordered layered compound formed by the hydrolysis of UTL in 0.1 M hydrochloric acid solution. Its structure is unsolvable by traditional X-ray diffraction techniques. The PDF technique was first benchmarked against high-quality synchrotron Rietveld refinements of IPC-2 (OKO) and IPC-4 (PCR) – two end products of IPC-1P condensation that share very similar structural features. An IPC-1P starting model derived from density functional theory was used for the PDF refinement, which yielded a final fit of R w = 18% and a geometrically reasonable structure. This confirms the layers do stay intact throughout the ADOR process and shows PDF is a viable technique for layered zeolite structure determination.